Effect of allopurinol on phosphocreatine recovery and muscle function in older people with impaired physical function: a randomised controlled trial. (21st April 2020) - Witham, Miles D; Clarke, Clare L; Hutcheon, Anita; Gingles, Christopher; Gandy, Stephen; Priba, Lukasz; Nicholas, Richard S; Cavin, Ian; Sumukadas, Deepa; Struthers, Allan D; George, Jacob
Abstract: Background: Allopurinol has vascular antioxidant effects and participates in purinergic signalling within muscle. We tested whether allopurinol could improve skeletal muscle energetics and physical function in older people with impaired physical performance. Methods: We conducted a randomised, double blind, parallel group, placebo-controlled trial, comparing 20 weeks of allopurinol 600 mg once daily versus placebo. We recruited community-dwelling participants aged 65 and over with baseline 6-min walk distance of <400 m and no contraindications to magnetic resonance imaging scanning. Outcomes were measured at baseline and 20 weeks. The primary outcome was post-exercise phosphocreatine (PCr) recovery rate measured using 31 P magnetic resonance spectroscopy of the calf. Secondary outcomes included 6-min walk distance, short physical performance battery (SPPB), lean body mass measured by bioimpedance, endothelial function and quality of life. Results: In total, 124 participants were randomised, mean age 80 (SD 6) years. A total of 59 (48%) were female, baseline 6-min walk distance was 293 m (SD 80 m) and baseline SPPB was 8.5 (SD 2.0). Allopurinol did not significantly improve PCr recovery rate (treatment effect 0.10 units [95% CI, −0.07 to 0.27], P = 0.25). No significant changes were seen in endothelial function, quality of life, lean body mass or SPPB. Allopurinol improved 6-min walk distance (treatment effect 25 m [95% 4–46, P = 0.02]). This was more pronounced in those with high baseline oxidative stress and urate. Conclusion: Allopurinol improved 6-min walk distance but not PCr recovery rate in older people with impaired physical function. Antioxidant strategies to improve muscle function for older people may need to be targeted at subgroups with high baseline oxidative stress.